Comparison of Intravesical Application of Chondroitin Sulphate and Colchicine in Rat Protamine/Lipopolysaccharide Induced Cystitis Model - sinanoglu, orhun; Dogan Ekici, Isin; Ekici, Sinan (Urology Journal, 2014)
Purpose: To investigate beneficial effect of the readily available colchicine through its intravesical application on protamine/lipopolysaccharide induced interstitial cystitis model in rat and to compare its efficacy to the chondroitin sulphate available for clinical use. Materials and Methods: Twenty-four Wistar female rats were assigned to control (C), interstitial cystitis (IC), chondroitin sulphate (CS) and colchicine (Col) groups. IC, CS and Col groups received protamine sulphate and lipopolysaccharide (PS/LPS) instillation. Testing agents CS and Col were administered a day after PS/LPS inoculation into the bladders. Rats in Group C received saline solution. CS and Col groups received 1 mL CS (0.2%) and 1 mL Col (0.05 mg/mL). The treatment agents were left in bladders for one hour’s duration. Animals were sacrificed 5 days after the inoculation and the bladder tissues were examined histologically to evaluate the amount of extravasated leucocytes, mast cell concentration (by counting total number of cells per 10 high power field (hpf; 1 hpf = ×400 magnification) as well as interstitial tissue edema for each bladder. Results: Intravesical application of CS reduced significantly the leucocyte and mast cell infiltration as well as interstitial edema compared to group C . The level of reduction in leucocyte and mast cell infiltration in Col group was comparable to that of CS, although the interstitial edema was not resolved. Conclusion: Intravesical administration of Col decreased leucocyte and mast cell infiltration to the same extent of CS in PS/LPS induced bladder inflammation in rat. Col may be an alternative to other treatment modalities for painful bladder conditions such as IC.